New highlights of the syntheses of pyrrolo[1,2-a]quinoxalin-4-ones - Georgescu, Emilian; Nicolescu, Alina; Georgescu, Florentina; Teodorescu, Florina; Marinescu, Daniela; Macsim, Ana-Maria; Deleanu, Calin (Beilstein Journal of Organic Chemistry, 2014)
The one-pot three-component reactions of 1-substituted benzimidazoles with ethyl bromoacetate and electron-deficient alkynes, in 1,2-epoxybutane, gave a variety of pyrrolo[1,2-a]quinoxalin-4-ones and pyrrolo[1,2-a]benzimidazoles. The influence of experimental conditions on the course of reaction was investigated. A novel synthetic pathway starting from benzimidazoles unsubstituted at the five membered ring, alkyl bromoacetates and non-symmetrical electron-deficient alkynes in the molar ratio of 1:2:1, in 1,2-epoxybutane at reflux temperature, led directly to pyrrolo[1,2-a]quinoxalin-4-ones in fair yield by an one-pot three-component reaction.
Keywords: 1,3-dipolar cycloadditions; multicomponent; one-pot three-component reactions; pyrrolo[1,2-a]benzimidazole; pyrrolo[1,2-a]quinoxalin-4-one